A VERY SHORT INTRODUCTION TO DIGITAL ARCHAEOLOGY - Schoueri, Kelly Marie Gillikin; Ferreira , Lucio Menezes (Notandum, 2020)
Visual reconstructions of archaeological sites and materials have been around since before the formal construction of archaeology as a discipline itself. However, there has been an expansion of the methods of reconstructing and representing the past in the last decades due to the use of digital technology. 3D modelling of archaeological sites and artifacts can generate aesthetically pleasing visualizations, but there is a danger of over-exaggerating or decontextualizing the past for public audiences. As digital artists and archaeologists, we should use caution with creating and disseminating archaeological visualizations. Considerations for scientific accuracy, ethics and educational value need to be taken into account. Therefore, this article introduces some of the theoretical issues involved with the digital reconstruction as well as an overview of the practical process of performing science-based archaeological 3D reconstructions and visualizations.